Learning to Lead: Foundations of Emerging Leader Identity Development. (August 2016) - Yeager, Katherine L.; Callahan, Jamie L.
The Problem: Organizations face several challenges that stand poised to place a significant strain on the availability of qualified leaders. Flatter organization structures, the use of more teams, and impending retirements of the Baby Boomer generation mean that the field of human resource development (HRD) must be prepared to help organizations develop the next generation of leaders. Scholars and practitioners must ensure that leader development initiatives will effectively prepare the forthcoming leaders from among young adults. The Solution: The focus of this study was to develop an understanding of how leadership experiences shape leader identity development. We offer a model that explains the dynamic, interactive process of leader identity development. Specifically, this model identifies the importance of relationships, leading by example, authenticity, and the motivation to lead for young adults. The Stakeholders: HRD scholars and practitioners may use the findings in this study to target developmental initiatives for future leaders.